Effective strategy execution : improving performance with business intelligence - Heesen, Bernd (Berlin : Springer Berlin, 2012)
Turbulent times create a threat for the survival of organizations while also offering new opportunities. This book uses many examples to demonstrate how an improved strategic management approach, leveraging established management concepts in conjunction with the innovative technology solutions offered by business intelligence, can lead to improved results. The book presents the three main barriers to an effective strategy execution and how they can be overcome. Creating a shared understanding of the strategy on all levels of the organization using a Value ScorecardTM and following the Strategic Alignment ProcessTM enables organizations to measure and monitor performance. The Strategic Alignment Remote ControlTM is presented as the ultimate tool for managers to remain in control of their business. Seven Case Studies from different industries across the globe provide examples how the organizational performance can be improved. They include companies like Daimler, Tetra-Pak, Wurth, Germany's Federal Employment Agency, City of Aix-Les-Bains, and Giesecke & Devrient. Additional examples from organizations like Disney, Marriott, Volkswagen, Avis, FedEx, and Harrahs help to demonstrate how the application of the introduced concepts adds a unique value. Additional details and the free Strategy Execution Effectiveness Survey are available at: www.strategicbusinessintelligence.com.
Includes bibliographical references and index.
Keywords: Business intelligence; Strategic planning